Complete genome sequence analysis of Edwardsiella tarda SC002 from hatchlings of Siamese crocodile - Rehman, Muhammad Nafees Ur; Dawar, Farman Ullah; Zeng, Jifeng; Fan, Lixia; Feng, Wei; Wang, Mengqi; Yang, Nuo; Guo, Guiying; Zheng, Jiping (Frontiers in Veterinary Science, 2023)
Edwardsiella tarda is a Gram-negative, facultative anaerobic rod-shaped bacterium and the causative agent of the systemic disease “Edwardsiellosis”. It is commonly prevalent in aquatic organisms with subsequent economic loss and hence has attracted increasing attention from researchers. In this study, we investigated the complete genome sequence of a highly virulent isolate Edwardsiella tarda SC002 isolated from hatchlings of the Siamese crocodile. The genome of SC002 consisted of one circular chromosome of length 3,662,469 bp with a 57.29% G+C content and four novel plasmids. A total of 3,734 protein-coding genes, 12 genomic islands (GIs), 7 prophages, 48 interspersed repeat sequences, 248 tandem repeat sequences, a CRISPR component with a total length of 175 bp, and 171 ncRNAs (tRNA = 106, sRNA = 37, and rRNA = 28) were predicted. In addition, the coding genes of assembled genome were successfully annotated against eight general databases (NR = 3,618/3,734, COG = 2,947/3,734, KEGG = 3,485/3,734, SWISS-PROT = 2,787/3,734, GO = 2,648/3,734, Pfam = 2,648/3,734, CAZy = 130/3,734, and TCDB = 637/3,734) and four pathogenicity-related databases (ARDB = 11/3,734, CARD = 142/3,734, PHI = 538/3,734, and VFDB = 315/3,734). Pan-genome and comparative genome analyses of the complete sequenced genomes confirmed their evolutionary relationships. The present study confirmed that E. tarda SC002 is a potential pathogen bearing a bulk amount of antibiotic resistance, virulence, and pathogenic genes and its open pan-genome may enhance its host range in the future.